IMPLEMENTATION OF PUBLIC SERVICES OF THE SUKABUMI SIAGA HEALTHY SOUL MOVEMENT (RASASEJIWA) AT THE SUKABUMI HEALTH CENTER IN SUKABUMI CITY - Adam Pebrian; Ike Rachmawati; Dian Purwanti (DIA: Jurnal Administrasi Publik, 2025)
This study aims to explore and understand the implementation of the Sukabumi Alert for Mental Health (RASASEJIWA) movement in public services at the Sukabumi Health Center, Sukabumi City. The implementation of this program is a crucial aspect in addressing the cases of People with Mental Disorders (ODGJ) in the region. This research used a qualitative method with a case study approach. Data was collected through interviews with various related parties, including Puskesmas staff, local government, and families of ODGJ patients. The analysis was based on 4 indicators from the Edward III implementation model: communication, resources, disposition, and bureaucratic structure. The results show that effective communication has been carried out between the Puskesmas and stakeholders, but there is still a need to simplify language and increase the depth of communication with the community. Resources such as specialist medical personnel and special facilities are still limited, requiring further support. The staff's disposition shows a high level of commitment, but additional training is needed. The clear bureaucratic structure supports the division of tasks, but inter-departmental coordination needs to be improved to enhance the consistency of information.